Detecting Face in video file and images - Mahale, Neelam; Nagmode, Manoj S (International Journal of Computer Sciences and Engineering, 2014)
Face detection is very first term face recognition. Find Face and feature of face has very important in many application such as face tracking, surveillance and security system etc. This paper presents a face detection technique which detects the faces in images and video file. It receives the images or video file from camera and detects the locations of face(s). This system uses Opencv library and VC 10.